Pengaruh Pendapatan Yang Diharapkan, Role Model, dan Self Efficacy Terhadap Minat Berkarir Akuntan Publik (Studi kasus Mahasiswa Akuntansi Universitas Islam Malang yang Sudah Menempuh Mata Kuliah Audit) - Faiz, Syahrul; Askandar, Noor Shodiq; Malikah, Anik (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to determine and analyze the influence of expected income, role models, and self-efficacy on interest in a career as a public accountant. Using multiple linear regression methods, this research focuses on explanatory research with a quantitative approach. The research sample of 82 respondents was taken using the Slovin formula. Data analysis was carried out with the help of SPSS version 26 software, including validity test, reliability test, normality test, classical assumption test, hypothesis test, and R2 coefficient of determination test. The research results show that overall, expected income, role models, and self-efficacy have a significant effect on interest in a public accounting career. Specifically, expected income, role models, and self-efficacy have a positive influence on interest in a public accounting career.Keywords: Expected income, role model, self efficacy, career interest